Prenatal and postnatal findings in five cases of Fryns syndrome. (22nd July 2014) - Peron, Angela; Bedeschi, Maria Francesca; Fabietti, Isabella; Baffero, Giulia Maria; Fogliani, Roberto; Ciralli, Fabrizio; Mosca, Fabio; Rizzuti, Tommaso; Leva, Ernesto; Lalatta, Faustina
<x xml:space="preserve">Abstract</x> What's already known about this topic? Fryns syndrome is characterized by congenital diaphragmatic hernia, facial dysmorphisms, distal digital hypoplasia, and variable cerebral, ocular, cardiovascular, and genitourinary malformations. It is often lethal. No causative gene is known, and the diagnosis is based on clinical findings. Data on prenatal diagnosis are lacking. What does this study add? This study demonstrates that prenatal diagnosis of Fryns syndrome is currently not possible in most cases. This finding has implications for prenatal genetic counseling and in utero treatment of diaphragmatic hernia.